Pengaruh Return On Asset (ROA), Return On Equity (ROE), Earning Per Share (EPS), dan Debt to Equity Ratio (DER) Terhadap Harga Saham (Studi Kasus Pada Perusahaan Sub Sektor Otomotif dan Komponen di Bursa Efek Indonesia (BEI) Periode 2014-2016) - Aris Utara; Ngatno Ngatno (Universitas Diponegoro, 2017)
The stock price is a form of public trust in the company’s performance. Stock price are influenced by two factors, that are the fundamental factor or factor related to the performance of a company and market factor (investors and potential investors trust), the factors that are determined from the external company. There are various sectors of open manufacture or manufaktur tbk listed in Indonesia Stock Exchange (BEI). One of them is the multifarious industry sector which consists of 7 sub-sectors of open manufacturing companies or manufaktur tbk. The automotive and component sub-sectors consissts of 13 open manufacturing companies or manufaktur tbk. In the last three years the automotive and component sub-sectors have fluctuated in the ROA, ROE, EPS, DER, and stock price so that investors have difficulty determining the decision indicator to invest.This type of research is an explanatory research, with the population that can be studied in the automotive and component sub-sectors with a total of 11 companies. The type of data source that used is the secondary data obtained indirectly. The type of data used in this study are time series data and cross section data or often referred as panel data. Methods of data analysis used are classical assumption, correlation, determination, simple regression, multiple regression, and signification test by using SPSS application.This study concludes that ROA and EPS have an effect on stock price, which mean ROA and EPS have increase, then stock price partially increase. While ROE and DER have no effect on stock price. Testing simultaneously shows ROA, ROE, EPS, and DER have an effect on stock price. If ROA, ROE, EPS, and DER increase, then the stock price increases as well.Based on that matter, the authors suggest that automotive and component sub-sectors companies should pay attention to indicators on ROA, ROE, EPS, and DER so stock price will increase. So that the investors are interested to invest their asset in the company.